Foot-and-Mouth Disease Virus Leader Protease Cleaves G3BP1 and G3BP2 and Inhibits Stress Granule Formation - Visser, Linda J; Medina, Gisselle N; Rabouw, Huib H; de Groot, Raoul J; Langereis, Martijn A; de Los Santos, Teresa; van Kuppeveld, Frank J M (Journal of virology, 2019)
Like other viruses, the picornavirus foot-and-mouth disease virus (FMDV; genus ), one of the most notorious pathogens in the global livestock industry, needs to navigate antiviral host responses to establish an infection. There is substantial insight into how FMDV suppresses the type I interferon (IFN) response, but it is largely unknown whether and how FMDV modulates the integrated stress response. Here, we show that the stress response is suppressed during FMDV infection. Using a chimeric recombinant encephalomyocarditis virus (EMCV), in which we functionally replaced the endogenous stress response antagonist by FMDV leader protease (L ) or 3C , we demonstrate an essential role for L in suppressing stress granule (SG) formation. Consistently, infection with a recombinant FMDV lacking L resulted in SG formation. Additionally, we show that L cleaves the known SG scaffold proteins G3BP1 and G3BP2 but not TIA-1. We demonstrate that the closely related equine rhinitis A virus (ERAV) L also cleaves G3BP1 and G3BP2 and also suppresses SG formation, indicating that these abilities are conserved among aphthoviruses. Neither FMDV nor ERAV L interfered with phosphorylation of RNA-dependent protein kinase (PKR) or eIF2α, indicating that L does not affect SG formation by inhibiting the PKR-triggered signaling cascade. Taken together, our data suggest that aphthoviruses actively target scaffolding proteins G3BP1 and G3BP2 and antagonize SG formation to modulate the integrated stress response. The picornavirus foot-and-mouth disease virus (FMDV) is a notorious animal pathogen that puts a major economic burden on the global livestock industry. Outbreaks have significant consequences for animal health and product safety. Like many other viruses, FMDV must manipulate antiviral host responses to establish infection. Upon infection, viral double-stranded RNA (dsRNA) is detected, which results in the activation of the RNA-dependent protein kinase (PKR)-mediated stress response, leading to a stop in cellular and viral translation and the formation of stress granules (SG), which are thought to have antiviral properties. Here, we show that FMDV can suppress SG formation via its leader protease (L ). Simultaneously, we observed that L can cleave the SG scaffolding proteins G3BP1 and G3BP2. Understanding the molecular mechanisms of the antiviral host response evasion strategies of FMDV may help to develop countermeasures to control FMDV infections in the future.